2022
DOI: 10.1177/00368504221117068
|View full text |Cite
|
Sign up to set email alerts
|

Body Shape Questionnaire-34 (BSQ) and Functionality Appreciation Scale (FAS) - pertinent body image screening tools: Creation and validation of Polish language versions

Abstract: Objective: Body image is defined as the perception of one's own body. While positive body image has a positive impact on quality of life, self-dissatisfaction may lead to depression, anxiety and low self-esteem. Body image might be quantified and evaluated: relevant instruments include the Body Shape Questionnaire (BSQ) and the Functionality Appreciation Scale (FAS). This study was designed to translate and evaluate the psychometric properties of the Polish versions of these instruments. Methods: Translation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The findings revealed a significant association between skin conductance response frequency and the presence of the BDNF Met genotype. In addition, the Body Shape Questionnaire (BSQ) was also used, which is a self-report tool that assesses body image concerns and dissatisfaction ( Yurtsever et al, 2022 ). According to the study, individuals with AN experienced more positive feelings when processing images of underweight bodies ( Clarke et al, 2016 ), suggesting that underweight stimuli evoked a distinct emotional reaction in patients with AN and could be related to their body image perception.…”
Section: Resultsmentioning
confidence: 99%
“…The findings revealed a significant association between skin conductance response frequency and the presence of the BDNF Met genotype. In addition, the Body Shape Questionnaire (BSQ) was also used, which is a self-report tool that assesses body image concerns and dissatisfaction ( Yurtsever et al, 2022 ). According to the study, individuals with AN experienced more positive feelings when processing images of underweight bodies ( Clarke et al, 2016 ), suggesting that underweight stimuli evoked a distinct emotional reaction in patients with AN and could be related to their body image perception.…”
Section: Resultsmentioning
confidence: 99%
“…Given that therapeutic interventions have been developed in the eld of EDs, which also focus on [7,48] or entirely address [8] functional aspects of body image to enhance body satisfaction, it is essential to be able to measure body functionality before, during and after these interventions. For this reason, we recommend, along with Yurtsever et al, [49], further research exploring the sensitivity to change of the FAS. Another limitation in our study was the disproportionate distribution of the various types of EDs in our clinical sample.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond factorial validity, most test adaptation studies have also shown that the FAS is invariant across gender identity (see also Marmara & Zarate, 2022), with gender differences in functionality appreciation generally non-significant or negligible (see Linardon et al, 2023). Moreover, where additional indices of validity have been tested (see also Yurtsever et al, 2021), studies have robustly supported the concurrent (e.g., positive associations with other facets of positive body image and negative associations with eating disorder psychopathology), convergent (e.g., positive associations with indices of psychological well-being, such as self-esteem and life satisfaction), and incremental validity of the scores on the FAS (e.g., functionality predicts psychological well-being over-and-above other indices of positive body image). Overall, these findings across national groups are consistent with the conclusions of a recent meta-analysis of the correlates of functionality appreciation, which found that functionality appreciation is consistently associated with fewer body image problems, lower levels of disordered eating, and more positive mental health (Linardon et al, 2023).…”
Section: Introductionmentioning
confidence: 99%